1986
DOI: 10.1111/j.1651-2227.1986.tb10303.x
|View full text |Cite
|
Sign up to set email alerts
|

Hip Joint Instability in Breech Pregnancy

Abstract: 222 consecutive fetuses found by ultrasound to be in breech presentation in the 33rd gestational week were followed with repeated examinations in weeks 35 and 38. Ninety-one of these fetuses persisted in breech presentation until delivery, while cephalic version occurred in 131. The frequency of hip joint instability was 21% in the breech delivered group and 1.5% in the vertex delivered group. The position of the fetal legs was established at each ultrasound examination. The intrauterine fetal attitude was cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
(13 reference statements)
2
9
0
Order By: Relevance
“…3 They have also not explored the difference between elective and emergency caesarean section nor used a multivariate analysis on all available data: conflicting results concerning the prevalence of DDH among vaginally delivered compared with caesarean delivered breech babies have been reported,12 16 28 some studies being limited by small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…3 They have also not explored the difference between elective and emergency caesarean section nor used a multivariate analysis on all available data: conflicting results concerning the prevalence of DDH among vaginally delivered compared with caesarean delivered breech babies have been reported,12 16 28 some studies being limited by small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that foetal breech position, rather than breech delivery, is a risk factor for hip instability. Extended breech was found to be worst for hip dysplasia (Luterkort et al, 1986). Foetal breech position has also been shown to have effects on limb movements and positioning after birth.…”
Section: Foetal Positionmentioning
confidence: 99%
“…2; extended (also known as frank) breech where the hips are in flexion and the knees in extension, flexed (or complete) breech where both hips and knees are flexed, and footling breech, where one or both feet come first. Luterkort et al (1986) performed repeated ultrasound scans on 222 foetuses in the breech position at 33, 35 and 38 weeks, and correlated leg positioning and delivery mode with hip instability. The authors found that foetal breech position, rather than breech delivery, is a risk factor for hip instability.…”
Section: Foetal Positionmentioning
confidence: 99%
“…The femoral head pressure acting against an immature fetal acetabulum may occur first. This may explain the high frequency of dislocations during postural abnormalities (breech, oligohydramnios, large for gestational age babies) [26,27].…”
Section: Discussionmentioning
confidence: 99%